La distinction procès vs résultat à l’exemple de substantifs verbaux (gerundia) et dérivés nominaux polonais - Kaliska, Agnieszka (Wydawnictwo Naukowe UAM, 2012)
The purpose of our research is to analyze the processual and the resultative reading of verbal nouns (gerundia) in Polish and to compare them with the corresponding standard derivational forms. Our research is based primarily on the analysis of the co-occurrence with the special kind of support verb named verbe support d’occurrence and the possibilities of using the plural, including the impact that the plural may have on the interpretation of verbal nouns and corresponding derivational forms.
Processual and resultative reading of verbal nouns (gerundia) and corresponding standard derivational forms in Polish